Râja Malla: Sebuah Kajian Resepsi - YB. Rahno Triyogo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
Râja malla: A Reception Study describes the events of text variations in Old Javanese Wirataparwa into New Javanese Wirataparwa. Text variation is creativity in which the reception of the text and its environment is reflected. Such incidents often occur in the text of wayang stories. Receptions can occur not only in the form of written text but also in the form of performing arts. The phrase râja malla in Old Javanese Wirataparwa underwent a shift in the New Javanese tradition in the form of written texts, and also in the form of performing arts. The reception referred to, first, is a shift in pronunciation from the Old Javanese tradition to the New Javanese tradition. Second, the shift in meaning, which originally meant the king of fights, has changed to the king of ‘disease’. Third, which was originally only a title or title which meant a fighting king, then in the New Javanese tradition it appeared as a personal name, namely Rajamala, a Wirata officer. Fourth, what was originally in the form of prose then changed in the form of song macapat, and in the form of performing arts with its various variants. The purpose of writing this article is to describe the process of the reception so as to produce new works based on existing works. The occurrence of text variation is described based on reception theory which holds that text variation occurs due to the principle of copyist freedom in copying text by reducing, changing or substituting words, phrases or episodes as deemed necessary. Another principle that is considered important is that every time there is copying, a new creation occurs. The steps taken to produce this article were by looking at or finding the development of texts from Old Javanese literature to New Javanese literature both in the form of written traditions and performing arts.